Sarcomatoid Chromophobe Renal Cell Carcinoma with Heterologous Component - Sushma Bharti; Gautam Ram Choudhary; Jyotsna Naresh Bharti; Garg Pawan Kumar; Arsha BS; Poonam Abhay Elhence (Iranian Society of Pathology, 2020)
Clear cellrenal cell carcinoma (RCC) is the most common malignant renal tumor in adults, while chromophobe RCC (CRCC) is the third most common. Any subtypes of RCC can undergo sarcomatoid differentiation, but heterologous differentiation in sarcomatoid area is very rare in RCC. Here a61-year male is presented with hematuria and palpable mass. Clinicoradiologically, RCC was considered and left radical nephrectomy was performed. A well-circumscribed renal mass located in the upper pole of the left kidney with variegation and extensive areas of bony hard calcification noted, was reported as CRCC with sarcomatoid differentiation containing heterologous component. CRCC subtype has good prognosis but show dismal prognosis when associated with sarcomatous differentiation.We found11 cases of sarcomatoid CRCC containing heterologous elements reported in indexed English literature. CRCC must be differentiated from Conventional RCC and Oncocytoma.The extensive sampling of the tumor is needed. We report a very rare case of CRCC with sarcomatoid differentiation containing heterologous elements.